Autobiographical fluency: a method for the study of personal memory. - Dritschel, B; Williams, J; Baddeley, A; Nimmo-Smith, I (1992)
Fifty-five subjects recalled autobiographical episodes or personal facts such as names of friends and teachers, from different lifetime periods. In each case, subjects were given 90 sec in which to retrieve as many items as possible. Also tested was subjects' fluency in generating items from semantic categories (animals, vegetables, British prime ministers, and U.S. presidents). Results of cluster analysis on the fluency tasks showed a dissociation between subjects' ability to retrieve personal episodes, personal semantic information, and nonpersonal semantic information. The dissociations observed in the fluency tasks are interpreted in terms of the different retrieval strategies required for the different types of information sought.